Energiewirksamkeit der Weizenproduktion unter semi-ariden Klimabedingungen: Zum Wechselspiel zwischen Energieeinsatz und -umsatz und geoökologischer und kulturtechnischer Variabilität in den zentralen Great Plains von Nordamerika - Späth, Hans-Joachim (ERDKUNDE, 1984)
Rising energy costs and decreasing energy availability force dry land farmers to improve their production energy budgets. Related innovations require information provided by detailed local and regional energy-input/output-analysis,which in turn are based on field-scaled monitoring of the daily flow of cultural energy-input and of food energy-output under the complete spectrum of tillage systems, reflecting the full range of geo-ecological variability. Available moisture, plant residue on the field surface, and soil texture are the dominant geo-ecological and agro-technical parameters to which energy-output/input-ratios and yield performance will be related to in this project. The energy-ratio, averaged for unfertilized and fertilized wheat, is 17.41 in the east and 10.77 in the west;related yields are at the 42.91 bu/acre (ca. 28,8 dz/ha) level in the east and at 31.58 bu/acre (ca. 21,2 dz/ha) in the west. -budgets, the traditional means for quantifying farm production performance, on the other hand result in output/input-ratios of no higher than 3 to 5. The regional and seasonal variation of energy efficiency and of yield is closely related to the pattern of distribution of rainfall and of available moisture and to the rate of remaining residue, a numerical resultant of the impact of tillage operations on plant residue rates on the field surface. Moisture and yield, energy ratios and moisture, yield and ratios, and remaining residue and moisture show strong correlations. The resulting individual equations are applicable as planning tools in areas with 11 to 20 inches (280 to 510 mm) of annual rainfall, between10 and 60 bu of wheat per acre (6,7 and 40,3 dz/ha), and at energy-ratio levels from 3 to 40.